Acute Hepatitis C Virus Infection Treated with Daclatasvir/Sofosbuvir in a 9-Year-Old Boy - Rahmani, Parisa; Farahmand, Fatemeh; Heidari, Ghobad (Journal of Child Science, 2022)
The present study includes a case report of a 9-year-old boy who came to our center with jaundice, elevated liver enzymes, and palpable liver. He was treated with ursodeoxycholic acid, but no improvement in symptoms was seen. Reverse transcription polymerase chain reaction and liver biopsy were positive for hepatitis C virus. He was treated with daclatasvir/sofosbuvir for 3 months. Daclatasvir/sofosbuvir might be effective against the treatment of hepatitis in children, with no report of remission and minimal side effects.
Keywords: hepatitis C; ursodeoxycholic acid; RT-PCR; liver enzymes